Survival camps in nature as a form of social skills training - Vukovič, Matej (Revija za elementarno izobraževanje, 2021)
This paper presents survival camps in nature as a form of social skills training. The camps are aimed primarily at adolescents with behavioural and emotional difficulties. They comprise many everyday social skills where both the group and the individual in the group are important. Social skills are among the many skills we teach in survival camps. Participants become acquainted with the content, methods and skills, and they strengthen the competences that help them to better integrate and function in the society. We shall present to what extent and in what way the social skills of young people are strengthened at survival camps, how young people gain vital experiences and competences and develop their potential.
Keywords: adolescents; groups; mladostniki; preživetje; skupine; social skills; socialne veščine; survival; training; treningi